Digital empowerment, organizational innovation, and social sustainability: A digital humanities perspective on women’s educational leadership in Egypt - Al-Dosari, Mashael Nasser Ayed; Abdellatif, Mohamed Sayed; Ahmed, Abdulaaty Abdulkarim M; Nemt-allah, Mohammed Ali (Research Journal in Advanced Humanities, 2026)
Digital transformation has reshaped educational institutions not only through technological change but also by redefining patterns of leadership, participation, and social inclusion. Within the framework of digital humanities, digital empowerment can be understood as a socio-cultural process that enhances individuals' capacity to participate in digitally mediated institutional environments and contribute to sustainable social development. Despite increasing interest in digital transformation, little empirical research has explored how digital empowerment and organizational innovation jointly influence social sustainability among women educational leaders in developing societies. This study investigates the predictive roles of digital empowerment and organizational innovation in fostering social sustainability among female school leaders in Egypt's Delta Region. Using a descriptive correlational design, data were collected from 284 female principals and vice principals working in elementary and middle schools across several governorates. Participants completed validated measures of digital empowerment, organizational innovation, and social sustainability. Pearson correlation coefficients and multiple regression analyses were employed to examine the relationships among the study variables. The findings revealed that digital empowerment significantly predicts social participation and social equity, while organizational originality emerged as the strongest predictor across all dimensions of social sustainability, surpassing organizational flexibility. Together, the predictor variables explained substantial proportions of variance in socially sustainable practices within educational settings. The study argues that digital empowerment should be viewed not merely as technological competence but as a cultural resource that strengthens women's leadership, institutional creativity, and inclusive social participation. By integrating perspectives from digital humanities and educational leadership, the findings contribute to understanding how digitally mediated organizational cultures can support social sustainability in contemporary educational communities. The study recommends embedding innovation-oriented digital empowerment initiatives within leadership development policies to promote socially inclusive educational institutions.